Halal principle and operational performance of MSMEs industries: Mediating role of lean six sigma and sustainability - Mohamad, Effendi; Faishal, Muhammad; Asih, Hayati Mukti; Abdul Rahman, Azrul Azwan; Johanuar, T.; Adiyanto, Okka (Penerbit UTeM, 2025)
Improving operational performance in MSMEs within Indonesia’s poultry industry is crucial, given the sector’s significant contribution to the national economy. However, it continues to face challenges related to Halal Principles (HP), process inefficiencies, quality issues, low product innovation, and adverse environmental and social impacts that may hinder economic growth. This study investigates the influence of HP on Operational Performance (OP), with Lean Six Sigma (LSS) and Sustainability (S) as mediating variables, in the context of Indonesia's poultry industry. Data from 249 randomly selected respondents were analyzed using Structural Equation Modelling (SEM) with IBM SPSS AMOS version 24.0. The results reveal that HP significantly affects both OP and S. LSS was found to have a direct impact on OP and partially mediates the relationship between HP and OP. Similarly, S directly influences OP and acts as a partial mediator between HP and OP, as well as between LSS and OP. The novelty of this study lies in the development of an inductive model, termed the Halal Lean Six Sigma Model (HLSSM), which theoretically connects HP, LSS, S, and OP. The findings confirm that HP, along with LSS and S, are key influencers of OP. These insights can guide MSME management in Indonesia’s poultry sector to strategically address the interrelationships among HP, LSS, and S to enhance operational performance.